Reproductive and productive performances of Kosali cattle in its native environment - Jain, Asit; Barwa, Deepti K; Singh, Mohan; Mukherjee, Kishore; Jain, Tripti; Tantia, M S; Rajam, K N; Sharma, Arjava (Indian Journal of Dairy Science, 2019)
Present study was conducted to record reproductive and productive performances of Kosali cattle maintained under farmer’s management conditions in Central Plain Region of Chhattisgarh state. 345 livestock owners were randomly selected and interviewed with structured questionnaire to obtain information on reproductive performance of Kosali cattle. Average age at first calving, calving interval, service period and number of services per conception were found 54.64±2.18 months, 430.26±6.33 days, 159.59±2.67 days and 1.4 ±0.08, respectively. In male, age at first ejaculation and age at first mating were found 41.54±1.14 and 51.3±1.05 months, respectively. Production was recorded and average daily milk yield, peak yield, lactation milk yield, lactation length and dry period were estimated to be 0.92±0.23 kg, 1.27±0.15 kg, 210.3±4.19 kg, 230.7±9.11 days and 190.8±8.19 days, respectively. Average fat and SNF percent were 4.4±0.27 and 10.41±0.21 %, respectively. Observed indices showed poor performances which are below the national average. Hence, suitable breeding strategies and training for livestock keepers and farmers on managemental aspects of Kosali cattle is needed to improve production and reproduction performances.